Olfactory Mucosa Mesenchymal Stem Cells Alleviate Cerebral Ischemia/Reperfusion Injury Via Golgi Apparatus Secretory Pathway Ca2+ -ATPase Isoform1 - He, Jialin; Liu, Jianyang; Huang, Yan; Zhuo, Yi; Chen, Wei; Duan, Da; Tang, Xiangqi; Lu, Ming; Hu, Zhiping (Frontiers in Cell and Developmental Biology, 2020)
Olfactory mucosa mesenchymal stem cells (OM-MSCs) have exhibited their effectiveness in central nervous system diseases and provided an appealing candidate for the treatment of ischemic stroke. Previous evidence showed that Golgi apparatus (GA) secretory-pathway Ca2+-transport ATPases isoform1 (SPCA1) was a potential therapeutic target for ischemic stroke. In this study, we explored the neuroprotective mechanism of OM-MSCs and its effect on the expression and function of SPCA1 during cerebral ischemia/reperfusion. Based on in vitro and in vivo experiments, we discovered OM-MSCs attenuated apoptosis and oxidative stress in ischemic stroke models, reduced cerebral infarction volume and improved neurologic deficits of rats. OM-MSCs also upregulated SPCA1 expression and alleviated Ca2+ overload, decreased the edema and dissolution of GA in neurons. Moreover, we discovered SPCA1 depletion in the OGD/R treated N2a cells mitigated the protective effects of OM-MSCs. Altogether, OM-MSCs exerted neuroprotective effects in ischemic stroke probably via modulating SPCA1 and reducing the edema and dissolution of GA in neurons.